Analisis Implementasi Marketing Public Relations (MPR) dalam Upaya Meningkatkan Penjualan Produk Tabungan Batara IB pada BTN KCPS Bukittinggi - Elpionita, Pindia; Mansur, Yuwarman (Lembaga Yasin AlSys, 2026)
The suboptimal implementation of Marketing Public Relations (MPR) at BTN KCPS Bukittinggi, marked by limited human resources, insufficient use of social media, and low public understanding of Islamic banking products, has affected fluctuations in sales of the Tabungan Batara iB product amid increasing competition among financial institutions. This study aims to analyze the implementation of Marketing Public Relations through various MPR activities in increasing sales of the Tabungan Batara iB product at BTN KCPS Bukittinggi. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The research informants consisted of the management and employees of BTN KCPS Bukittinggi as well as several customers. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of Marketing Public Relations at BTN KCPS Bukittinggi had been carried out through several activities, namely publications, events, sponsorship, community service, and identity media. However, its implementation was not yet fully optimal because it still faced obstacles in the form of limited human resources specifically handling MPR, insufficient use of social media, and low public understanding of Islamic banking products. The conclusion of this study affirms that MPR optimization is needed to strengthen marketing communication, improve public understanding, and support sales of the Tabungan Batara iB product. These findings provide practical implications for BTN KCPS Bukittinggi in strengthening public relations-based marketing communication strategies, particularly through increasing human resource capacity and using social media more effectively.